Do not underestimate the blood urea nitrogen-to-creatinine ratio in heart failure. (11th May 2021) - Borges-Rosa, J; Campos, GM; Martinho, S; Almeida, JL; Goncalves, V; Ferreira, C; Freitas, AA; Milner, J; Ferreira, JA; Marinho, V; Alves, PM; Oliveira-Santos, M; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: The blood urea nitrogen-to-creatinine ratio (BUN/SCr) has been proposed as a prognostic marker in heart failure (HF). We aimed to evaluate whether BUN/SCr predicts mortality outcomes in a real-world Southern European population with decompensated chronic HF. Methods: We retrospectively studied 1057 patients with chronic HF admitted to our emergency department between November 2016 and December 2017 with acute decompensation. We excluded patients with a GFR <15mL/min/m2 or on dialysis. The incidence of cardiovascular (CV) and all-cause death was evaluated through multivariable logistic regression models and by Kaplan-Meyer survival curves. Results: 1025 patients were included, median age 80 years (IQR 73-85), 52.4% male, mean LVEF 42.8 ± 12.7%, and mean GFR 57.2 ± 23.9 mL/min/m2. Mean BUN/SCr was 24.9 ± 8.2 and mean SBP was 139 ± 29mmHg (r=-0.17, p < 0.001). After a median follow-up of 5 months (IQR 3-11 months), CV and all-cause death occurred in 8.0% and 21.6%, respectively. Mean BUN/SCr was higher in patients with fatal outcomes both for CV (31.3 vs. 24.3, p < 0.001) and all-cause death (28.6 vs. 23.8, p < 0.001). BUN/Scr was grouped by terciles: T1 (<20.78), T2 (20.78-27.15), T3 (>27.15). In the T3 group, the multivariable-adjusted  OR for CV and all-cause death was 5.43 (95% CI 2.20-13.37) and 2.72 (95% CI 1.66-4.46), respectively, compared to the T1 group. No significant differences between T1 and T2 groups. Conclusions: BUN/SCr at admission predicts CV and all-cause death in patients with chronic HF after an episode of decompensation. BUN/SCr, as an easy-to-use tool, helps to identify those patients who benefit from tight monitoring both during hospitalization and after discharge.